Desenvolvimento de secador tipo cesto rotativo para a secagem de folhas de eucalipto (Corymbia citriodora) - Freitas, Juliana Vieira de (2015)
The objective of this work is the development of a rotary type dryer for drying leaves. This dryer was built with the purpose of ensuring a proper mixing of the leaves during drying, to obtain a final product with homogeneous moisture and good quality. The dryer consists of a cylinder built with perforated metal screen, coupled to a motor which allows its rotation around the cylinder axis. Air supplied by a blower is heated and fed through the cylinder side walls, perpendicularly to its axis. For drying of eucalyptus leaves, it was evaluated the reproducibility of the data and the homogeneity of the rotary drying basket in comparison to fixed-bed drying configurations using different forms of contact between the air and the material, and also to the conventional rotary drum dryer. To evaluate the quality of the final product, it was analyzed the influence of drying in color of leaves, extracted oil content and the concentration of citronellal in the oil. The kinetic data showed good reproducibility between the repetitions in the range of conditions investigated. It was observed that the set of leaves increased in volume during drying in the rotating basket, and the whole volume of dried leaves was 3-fold the fresh leaves volume. The tests indicated that the rotating basket provided uniform drying of the leaves as compared to drying in fixed beds and conventional rotary drum dryer, with small variation of moisture and average final moisture of 7.3 ± 0.3 % in drying of 50 g of leaves. For a good performance in drying eucalyptus, the volume of fresh leaves should not exceed 10% of the basket volume. The drying in the rotating basket have not provoked browning of the leaves and did not influence the essential oil content.